From the margins to the mainstream: Community restorative justice in northern ireland. Issue 2 (August 2013) - Knox, Colin
Paramilitary organisations exerted a stranglehold on working class loyalist and republican communities in Northern Ireland during the conflict there. In the absence of an effective and legitimate policing service, paramilitaries developed an alternative 'justice' system in which they 'punished' those accused of committing crimes against the community. They adopted a punitive system of control which included threats or warnings, public humiliation, curfew, exiling, beatings and shootings. This article traces the evolution of this system from illegal paramilitary 'policing' through to restorative justice schemes offering non-violent alternatives to community crime, which, over time, have become a recognised part of the formal criminal justice system. Specifically, it examines the role that a series of evaluations had on influencing this transformation. At the very least, policy evaluation informed the political debate and provided evidence to move restorative justice from illegal activities to an integral part of the criminal justice system.